Pengolahan Data Akuntansi Keuangan Pada PT. Aldimana Solusi Teknologi Menggunakan Accurate Online Versi 1.0.0 - Haryanti Haryanti; Elin Panca Saputra (LPPM Universitas Bina Sarana Informatika, 2022)
The development of information technology in the world makes a situation of intense competition in the business world so that it requires every company to run its business more effectively. In the era of increasingly rapid technological developments, all fields of activity are computerized, one of which is accounting. PT Aldimana Solusi Teknologi is a company engaged in the trading of goods and services. This company is a new company so that in managing its financial data it still uses a manual system and has not used an accounting application, so that in terms of accounting records until the preparation of financial reports, errors in recording often occur, less the accuracy of the reports that have been made and takes a long time in the process of searching for the required data. The use of Online-Based Accurate Accounting is the right solution to solve problems that occur within the company. The use of Accurate Accounting helps record transactions more easily and efficiently so as to produce financial reports more quickly, precisely and accurately. It is expected that the use of this Accounting Software can facilitate companies in managing financial data so as to support company activities.